2011
DOI: 10.1097/rti.0b013e3181e35823
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Follow-up of Fibrosing Interstitial Pneumonia

Abstract: The extent of honeycombing at baseline and its progression on follow-up CT are important determinants of rate of survival in patients with fibrosing interstitial pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…H wang et al . [ 61 ] found that increasing honeycombing in patients with F-ILD on serial HRCT (in addition to the existence of honeycombing at baseline HRCT) over 1 year predicted mortality, although the same was not denoted by lung function measurements.…”
Section: Section 2: Prognostication and Monitoringmentioning
confidence: 99%
“…H wang et al . [ 61 ] found that increasing honeycombing in patients with F-ILD on serial HRCT (in addition to the existence of honeycombing at baseline HRCT) over 1 year predicted mortality, although the same was not denoted by lung function measurements.…”
Section: Section 2: Prognostication and Monitoringmentioning
confidence: 99%
“…While a categorical FVC decline of ≥10% has been associated with an increased mortality risk in patients with IPF ( 16 19 ), CHP ( 20 22 ), and CTD-ILD ( 23 ), even modest FVC decline of≥5% decline has been linked to worse outcome in IPF ( 16 ). Baseline extent of fibrosis on high-resolution computed tomography (HRCT) has been linked to prognosis in different ILD subtypes ( 24 , 25 ), even in the absence of FVC decline ( 26 ), and suggests that longitudinal increase in fibrosis extent is a good measure of progressive ILD ( 25 , 27 , 28 ). Symptomatic worsening, either alone or in combination with FVC decline or fibrotic progression on HRCT also suggests ILD worsening, but has yet been to validated as a reliable predictor of outcome.…”
Section: The Pf-ild Phenotypementioning
confidence: 99%
“…When comparing images side-by-side, it is important to ensure that equivalent anatomical slices are evaluated, especially when changes are marginal. Using such a simplified approach, Hwang et al [20] examined 72 patients with a variety of fibrotic interstitial lung diseases. They found 36% of patients showed HRCT worsening of fibrosis, with follow up CT at a median of 1 year from baseline.…”
Section: Computed Tomography and Progressive Phenotype Of Interstitia...mentioning
confidence: 99%